Utilization of Xylanase Enzymes Derived from Cassava in the Eco-Friendly Biobleaching of Pulp - Ahmad Muhammad Fuadi; Dita Aulia Az Zahra; Saniya Farha; Krisna Artur Kunarfian; Tiara Nilawati Dewi; Dwi Susanti (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2024)
The demand for paper has been increasing over time, leading to the pulp and paper industry becoming one of the largest contributors to global carbon emissions due to the chlorine-based bleaching process, particularly in Indonesia. An alternative to minimize chlorine usage involves using xylanase enzymes as part of the bleaching sequence. Xylanase can be produced from agricultural waste, including cassava residue, which contains a significant concentration of xylanase, approximately 21.3%. However, it still needs to be utilized in Indonesia. Therefore, this study aims to explore the production of xylanase enzymes from cassava residue and assess its effectiveness in the biobleaching process of pulp. The research methodology includes the production phase of xylanase enzymes by Aspergillus niger, chelating, bleaching sequence, bleaching, kappa number, and chemical saving assay. In the production of xylanase, the study determined that xylanase exhibits optimal activity under specific conditions, notably at a pH of 6 and a temperature of 60°C. Under these parameters, the enzymatic activity reached a level of 0.4986 U/mg protein. During the bleaching sequence, xylanase was used with doses of 0.3, 0.5, 0.7, 0.8, and 1 L/T pulp at 40, 45, 50, 55, 60, 65, and 70°C for 60 minutes. Following this process, bleaching was conducted at 65°C for 70 minutes, extraction at 80°C for 90 minutes, and a second bleaching phase. Subsequently, a kappa number test was performed, revealing the best kappa value at 60°C with a xylanase dose of 0.5 L/T pulp, reducing from an initial kappa number of 9 to 4.04. Additionally, under these conditions and dosage, xylanase enzymes could save approximately 23.67% in chlorine usage